Uji Eksperimental Efisiensi Panas Alat Pengering Surya Langsung Pasif Berbiaya Murah dengan Variasi Material Penutup Transparan - Kemas Muhammat Abdul Fatah (Infotekmesin, 2022)
Indonesia, with the availability of sunlight almost all year round, for spreading throughout Indonesia of solar dryer usage requires an inexpensive and durable. This study proposes a passive direct solar dryer because the simplest in construction, with aluminum mesh sheets as a heat-absorbing material, glass fiber as an insulating material. For the transparent cover, considering cost, durability, α value, and τ value, this study proposes 0.8 mm clear polycarbonate (PC), 2 mm clear glass, and 2 mm clear acrylic. From the experimental test results of the solar dryer model, the highest heat efficiency value for polycarbonate (PC) is 16%, the heat efficiency value for glass and acrylic is 10% and 8%, respectively. With these findings, the construction of solar dryers is simple, low cost, and durable, insulation uses glass fiber, heat absorbers use aluminum mash sheets, and transparent covers use PC instead of using glass in common with thinner sizes.